Synthesis and characterization of electrochemical ZnO sensor using horizontal vapor phase crystal (HVPC) growth technique for detecting aflatoxin - Olarve, James Salveo L. (Animo Repository, 2022)
Aflatoxin (AF) is a secondary metabolite from the molds Aspergillus flavus and Aspergillus parasiticus. These toxins are regarded as human carcinogens because they are particularly harmful to the liver, according to the International Agency for Research on Cancer (IARC). They contaminate mainly our crops because they are found on the ground. The most widely accepted method for AF detection is high-performance liquid chromatography (HPLC). However, this method is time-consuming, expert dependent, expensive, and difficult to handle. As such, easy and economical detection of AF is a must. One promising approach for AF detection is via the electrochemical method using nanomaterials. Since nanomaterials have a large surface-area-to-volume ratio, their sensing capabilities are heightened, enabling the detection of small molecules, such as AF. The researcher synthesized ZnO nanowires on a silica substrate via the horizontal vapor phase crystal (HVPC) growth technique. Then, the specimens were subjected to various characterizations, such as surface morphology (SEM), elemental (EDX), contact angle measurements, current-voltage graph, and resistivity. It was found that 95% of the ZnO nanowires have a diameter of less than 100nm. The EDX results showed the purity of the material. The deposited ZnO nanowires on the silica substrate are hydrophobic (113.01°) and have a bulk resistivity of 0.020 Ω-m. The electrochemical sensor was made using ZnO nanowires as the working electrode, while the reference electrode is Ag/AgCl, and the counter electrode is carbon. The highlights of this study are adopting the drop method instead of the commonly used dip method, using fewer reagents in AF detection, and utilizing ZnO nanowires. The cyclic voltammetry measurements were straightforward on a water-acetonitrile solution mix with four types of AF. The ZnO nanowire electrochemical sensor successfully detects AF from 5% to 50% of the purchased AF solution concentration. The sensor’s response is linear to that range of AF concentration. Moreover, the sensor’s detection limit is lower than 20 ppb for a small volume of AF solution (10 microliters) with a fast measurement time (57.14 sec). According to the US Food and Drug Administration guidelines, the highest limit of AF concentration on corn safe for human consumption is 20 ppb. Therefore, since the detection limit of the sensor is under 20ppb, it is an excellent sensor capable of determining whether a sample has a lower than the maximum permitted AF concentration.